2009
DOI: 10.1002/elps.200900017
|View full text |Cite
|
Sign up to set email alerts
|

Dielectrophoretic focusing of particles in a microchannel constriction using DC‐biased AC flectric fields

Abstract: This paper presents a fundamental study of particle electrokinetic focusing in a single microchannel constriction. Through both experiments and simulations, we demonstrate that such dielectrophoresis-induced particle focusing can be implemented in a much smaller magnitude of DC-biased AC electric fields (10 kV/m in total) as compared to pure DC electric fields (up to 100 kV/m). This is attributed to the increase in the ratio of cross-stream particle dielectrophoretic velocity to streamwise electrokinetic veloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
161
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 116 publications
(174 citation statements)
references
References 50 publications
11
161
1
Order By: Relevance
“…3B. This is believed to be a consequence of the constriction-induced dielectrophoretic focusing effect on 590 nm particles as we have demonstrated previously [25].…”
Section: Numerical Methods and Materials Propertiessupporting
confidence: 60%
See 2 more Smart Citations
“…3B. This is believed to be a consequence of the constriction-induced dielectrophoretic focusing effect on 590 nm particles as we have demonstrated previously [25].…”
Section: Numerical Methods and Materials Propertiessupporting
confidence: 60%
“…Using our previously developed model [20,25], we estimated the potential influence of DEP on the trajectories of the 590 nm tracing particles in the above experiment. It was found that the induced dielectrophoretic velocity was on the order of 50 mm/s in the fluid circulation regions, and could reach 150 mm/s if the particle was within 2 mm distance from the corners of the constriction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5][6] The success of these electrically controlled microfluidic devices for particle transport relies on a comprehensive understanding of fluid and particle behavior in these devices. However, most existing theoretical [7][8][9][10][11] and experimental [12][13][14][15][16][17][18][19] studies on the electrokinetic transport in microfluidic devices have been performed exclusively on spherical particles. In fact, a large amount of particles used in microfluidic applications, such as biological entities 1 and synthetic nanowires, 20,21 is nonspherical.…”
Section: Introductionmentioning
confidence: 99%
“…11,15 Dielectrophoresis refers to a nonlinear electrokinetic phenomenon 30 in which a force is exerted on a dielectric particle when it is subjected to a spatially nonuniform electric field. This kind of electrokinetic phenomenon has been widely used to manipulate spherical particles in microfluidics such as particle trapping, [31][32][33][34][35] separation, 16,[35][36][37][38][39][40][41] focusing, 14,18,35 and cell discrimination. 42,43 Previous numerical and experimental studies demonstrate that the DEP effect should be taken into account to study the electrokinetic transport of spherical particles where nonuniform electric fields are present.…”
Section: Introductionmentioning
confidence: 99%